Spain : Financial Sector Reform: Third Progress Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper presents the Third Progress report on Spain's financial sector reform. Correction of Spain's large external, fiscal, and financial imbalances is well underway, with policy actions at both the European and Spanish levels helping to ease market pressures over the last year. Financial sector dynamics still contribute to recessionary pressures, with credit contraction accelerating, lending standards tightening, and lending rates to firms rising. Actions taken by the authorities under the European Stability Mechanism-supported program have helped tackle the legacy risk from the real estate boom bust, but macroeconomic risks still loom large.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet